The effects of the bologna process on college enrollment and drop-out rates - Julia Horstschräer; Maresa Sprietsma (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper estimates the short-term effects of the introduction of the Bachelor degree in the framework of the Bologna Process on college enrollment and drop-out rates. We use variation in the timing of the Bachelor implementation at the department level to identify the effect of the reform based on longitudinal administrative student data from Germany. We find no significant effects on college enrollment or drop-out rates for most subjects.
Keywords: I28; I21; C23; 330; higher education; college enrollment drop-out; Bologna Process; Hochschulreform; Bildungsabschluss; Studierende; Bildungsverhalten; Abbrecher; Deutschland